Language supports for children's understanding of numerical fractions: Cross-national comparisons. - Miura, Irene T.; Okamoto, Yukari; Vlahović-Štetić, Vesna Kim, Chungsoon C.; Han, Jong Hye (1999)
This study examined Croatian, Korean, and U.S. children's knowledge of numerical fractions prior to school instruction. The research is part of an ongoing project examining the influence of language characteristics on mathematical thinking and performance. The part-whole quantitative relation denoted by numerical fractions may be easier to understand in East Asian languages like Korean. In these languages, the concept of fractional parts is embedded in the mathematics terms used for fractions. The results from this study suggest that the Korean vocabulary of fractions may influence the meaning 6- to 7-year-old children ascribe to numerical fractions and that this results in children being able to associate numerical fractions with corresponding pictorial representations prior to formal instruction.
Projekt MZOS
ENG